فعالية تنظيف نواتج الاحتراق من SO2 باستخدام أجهزة الامتصاص الرغوية دراسة تجريبية ومحاكاة رقمية - عواطف نصره (Tishreen University, 2016)
يهدف البحث إلى إيجاد طريقة لحساب المميزات الهيدروديناميكية والحرارية لأجهزة الامتصاص الرغوية المستخدمة في الطرق الرطبة لتنظيف نواتج الاحتراق من SO2من أجل زيادة فعالية واقتصادية هذه الطرق. لذلك تمت دراسة التبادل الحراري والهيدروديناميكي لجهاز الامتصاص ذو الطبقة المتحركة الثنائية الطور (الرغوية) مع نماذج مختلفة من أجهزة التلامس، وعلى أساس المعطيات التجريبية والتحليل الرياضي لها تم الحصول على المعادلات التي تسمح بتقييم تأثير العوامل الظرفية في المتغيرات الأساسية لطبقة الرغوة. كما تمَّ التأكيد على أن التبادل الحراري في مجال طبقة الرغوة يتميز بفعالية عالية للتبادل الحراري بين الغاز والسائل في طبقة الرغوة، وبين طبقة الرغوة والسطح المغمور. وأن معامل انتقال (تبادل) الحرارة بالحمل يتوقف على الشروط الابتدائية للطور الغازي والسائل وعلى فرق درجات حرارة نقطة الندى للغازات والسائل عند مدخل جهاز الامتصاص. بالنسبة لفعالية تنظيف غازات الاحتراق من SO2 فإن درجة التنظيف في الحدود العليا للنظام الرغوي نصل إلى (95,95%) خلال مرحلة تلامس واحدة. سمحت الدراسة أيضاً بزيادة الوثوقية لنظام التنظيف الرطب عن طريق اختيار التصميم الأمثل وذلك على أساس النتائج التي تمَّ الحصول عليها. The research aims to find a way to calculate the hydrodynamic and thermal characteristics of devices absorption foam used in the wet roads to clean the combustion products of SO2 to increase the effectiveness of these methods and economic. For it has been studied heat exchange and hydrodynamic device absorption with bilateral phase moving layer (foam) with different models of contact devices, and on the basis of experimental data and mathematical analysis have been obtained equations that allow assessment of the impact of contextual factors in the core layer foam variables. It was also stressed that the heat exchange in the field of foam layer is characterized by high efficiency heat exchange between the gas and the liquid in the foam layer and between the foam layer and the surface submerged, and give the temperature coefficient depends on the initial conditions of gaseous and liquid phase and the temperatures of the dew point of the gas and liquid teams at the entrance device absorption. As for the effectiveness of cleaning the combustion gases from the cleaning degree of SO2 in the upper border of the foam system up to (95,95%) on stage touches one. The study also allowed increase reliability for wet cleaning system by selecting the optimum poisoning and on the basis of data obtained.